Peliosanthes longicoronata (Asparagaceae), a new species from central Vietnam - Vislobokov, Nikolay A.; Tanaka, Noriyuki; Kuznetsov, Andrey N.; Kuzmicheva, Evgeniya A.; Romanov, Mikhail S. (Phytotaxa, 2018)
Peliosanthes longicoronata is described and illustrated as a new species from central Vietnam (Ha Tinh Province, Vu Quang National Park). The new species has comparatively long staminal corona, that is mentioned in the specific epithet. The new species resembles P. teta, but differs in its solitary, upward-facing flowers and a white, tubular, distally incurved staminal corona.